ریاست پاکستان کے نصاب اور مراکز تعلیم کا سیرت رسول اللہ ﷺ کی روشنی میں تجزیاتی مطالعہ: An Analytical Study of the Curriculum and Educational Institutions of the State of Pakistan in the light of the Prophet’s Seerah (PBUH) - Dr. Navid Iqbal (Al Manhal Research Journal, 2022)
Education is the biggest factor of change in any society. The education sector needs the most investment in underdeveloped countries. The state-sponsored curriculum reflects the state narrative. The state-sponsored curriculum is covered by the government narrative. Curriculum is an important component of the education system and plays a central role. Other structural components of the system, including teachers, students, and educational institutions, also have roles that are essentially set by the curriculum. The guiding principles of our state policy are enshrined in the constitution, from which every government has been enjoying 'custom'. The education policy of the state lays down the goals of the system and the curriculum required for it. The curriculum determines the teaching methods, teaching materials, teaching activities and teaching objectives. The education system of every state includes the national needs, time requirements and the sensitivity of the situation in its curriculum. Therefore, it is the responsibility of the state to prepare the education curriculum keeping in mind the needs of the time and in it immorality. and not include illegal content. Due to which the young generation of the state will suffer loss from moral and social aspects. Therefore, it is necessary that our education curriculum is such that it is prepared keeping in mind the needs of the time and does not include any material against the teachings of Islam. In this paper, an attempt has been made to explain the nature and character of the state's educational curriculum and educational institutions in the light of the Prophet's Prophet (PBUH).